Deterrence: A Security Strategy against Non Traditional Security Threats to Pakistan - Syed, Farzana Zaheer; Javed, Saba (International Journal of Social Sciences and Management, 2017)
Deterrence as an approach aims to prevent a non-state actor who is planning to threat and harm a nation state externally and internally. The present study designed to find out that to what extent Deterrence as security strategy is effective against non-traditional threats in Pakistan?, and Whether the deterrence as security strategy remains effective against non-traditional threats of terrorism and cyber threats in Pakistan? The world has redefined and reorganized the security strategies after 9/11terroists attacks. The fourth wave in the deterrence theory has extended the deterrence security concept and added up the non-traditional threats as necessary part in security planning. Non-Traditional threats, terrorism, ambiguous warfare, cyber threats, water security, human security and energy crises etc now have equal importance with the border security. To protect the state from these actors, Pakistan is now reassessing and reorganized its security strategies. But these policies need more deliberate efforts to deal with such internal and external factors that are slowly and constantly weakening the state. Int. J. Soc. Sc. Manage. Vol. 4, Issue-4: 267-274